PENGARUH PEMBERIAN EKSTRAK ALKOHOL AKAR ILALANG {Imperata cylindrica L.) TERHADAP PENURUNAN SUHU TUBUH TIKUS PUTIH JANTAN - Chairul Chairul (BERITA BIOLOGI, 2000)
Antipyretic effect of alcohol extract ofilalang flmperata cylindrica L) root on white rat males had been studied using fever tolerance method.Experimental animals were induced to fever by injecting 0.9 ml/kg BW vaccine kotipa orally.Alcohol extract 5, 10, 30, 50,100 and 150 mg/kg BW was given one hour after injection.The body temperature was measured before injection and every half an hour until the fifth hour after injection.Paracetamol 200 mg/kg BW was used as control.Data were analyzed using ANOVA with the body temperature (T), the time interval (P) and extract doses being given (C) as parameters.The results showed that body temperature increased TC from the basal temperature at the third hour after injection of vaccine.The body temperature did not change significantly at the lower extract doses(5-30 mg/kg BW)(P>0.05),while higher doses (30-150mg/kg BW) linearly lowered the body temperature significantly (P<0.05).The extract dose at 50 mg/kg BW lowered the body temperature similar to paracetamol 200 mg/kg BW.